Students' perception towards field study activity. (April 2020) - Permana, A; Saefudin,; Amprasto,
Abstract: This preliminary research aims to give description about students' perception towards field study or about the reasons for students like or dislike field study activity which has been occurred at schools and the potency to conduct field trip learning. This research used quantitative survey research method with deep explanation. The data collection used questionnaire and interview. The statements in the questionnaire were open and close statements, which showed positive and negative perception with 5 point-Likert scales. Index of appreciation of field study were determined using questionnaire information from 19 students in 12 th grade. The result show that out of 19 respondents, most of the express positive perception towards field study with average indices = 57.06 (range 45.45 – 81.82; with standard deviation = 8.48). The students' positive perception towards field study activity implies can give impact toward field skills acquisition such as identification or classification skills, monitoring or sampling or survey skills, teamwork skill, and problem-solving skills in the field.